Exploring the process and experiences of nursing care of patients at the end of life: nurses’, patients’, and family carers’ perspectives - Khalid, Dalhat Sani (2019)
Background: Nurses, patients, and family carers in Nigeria face several challenges associated with inadequate resources to care for patients at the end of life. This is evidenced in the recent ranking of palliative and end-of-life care across the world for the 2015 Quality of Death Index by the Economist Intelligence Unit; where Nigeria is at the position 77out of 80 countries. There is a dearth of literature relating to palliative and end-of-life care in Nigeria. A systematic review of end-of-life care in sub-Saharan Africa reveals that most of the studies in sub-Saharan Africa (SSA) were centred on HIV/AIDS, and the majority were in South Africa. No studies were from Nigeria nor found to explore the nurses’ experiences and understanding of caring for patients in hospitals during the end of life. To the researcher’s knowledge, this is the first study to explore the process and experiences of nursing care of patients at the end of life in a hospital from the perspective of nurses, patients, and family carers which justifies the current study.